Self-assembled antioxidant enzyme-mimicking hydrogel: Targeting oxidative stress and macrophage organization for improving degenerated intervertebral discs - Yudong Fu; Hua Sun; Yongchao Jin; Shaohui Cheng; Yanyi Wu; Chen Liu; Lei Fan; Juqun Xi; Shixin Li; Liang Zhang (Materials Today Bio)
Intervertebral disc degeneration (IVDD) is a major contributor to lower back pain. At present, antioxidant therapy is regarded as one of the most promising strategies for treating IVDD, due to the critical role of reactive oxygen species (ROS) in its pathogenesis. Herein, we presented a self-assembled hydrogel, termed MnGAHs, formed through the crossing of manganese ions (Mn2+) and glycyrrheic acid (GA), which possessed the activities of antioxidant enzymes, including catalase (CAT) and superoxide dismutase (SOD). The obtained MnGAHs effectively scavenge ROS, reducing oxidative stress levels and alleviating the senescence of nucleus pulposus-derived mesenchymal stem cells (NPMSC), thereby mitigating IVDD. Furthermore, MnGAHs also promoted macrophage polarization towards M2 phenotype, reducing the inflammatory response and thereby inhibiting the progression of IVDD. By combining theoretical calculations with analyses of public databases, we revealed that the ROS-p53-p21 axis played a crucial role in the function of MnGAHs to reverse IVDD, a finding further confirmed by Western blot analysis. As a result, the injection of MnGAHs into the intervertebral disc (IVD) significantly alleviated the degeneration process in a rat model of puncture-induced IVDD. Therefore, the as-prepared antioxidant enzyme-mimicking hydrogels provide a promising and effective approach for treating IVDD.